A Study of Location Model for a Rescue Vehicle Parking Stations: Case Study of Kannayao District in Bangkok - Jansuwan, Sarawut; Teeraprasert, Soravit (Journal of Applied Statistics and Information Technology, 2019)
The emergency service by rescue cars performs more significant role nowadays in helping victims in several accidents in the urban area. The objectives of this research aims to develop the location model to locate the suitable stand-by rescue cars parking stations in Kannayao District, Bangkok. The coverage distance from rescue car parking station to the accident should be within three kilometer. The accident data was collected from the field during day and night periods so that they reflect the variation of accidents’ location daily. Two location models including set covering and maximum covering are used to identify the most suitable locations. The demand weighted accident severity is used for the objective function for maximum covering model. The results indicate the new locations for rescue car parking station could reach to the accident effectively. The model could be further used for other urban areas.